Antioxidant And Antibacterial Activities Of Methanol Extract Of Fig Fruit And Leaves (Ficus Carica L.) - Agustina, Eva; Lusiana, Nova; Purnamasari, Risa; Faidah, Nurul Ilmi; Agustin, Azlinda Mitha (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
Background: Fig plants (Ficus carica L.) have phytochemical contents such as polyphenols, flavonoids, and anthocyanins which are relatively high. The content of this active compound can be used as an antioxidant and antibacterial. Objectif: The study aims to determine the antioxidant and antibacterial activity of methanol extracts fruit and leaves of fig (Ficus carica L.). Methods : DPPH method was carried out to determine the antioxidant fruit and leaves of fig (Ficus carica L.) by observing the change in colour of the test sample after incubation with DPPH solution using a UV-Vis spectrophotometer at a wavelength of 517 nm. The antibacterial test uses disc paper diffusion test to see the inhibition zone formed and continued with the MIC and MKC tests. Results : The antioxidant test results showed the IC50 values in methanol extracts of fig fruits were 13.402 ppm and 7.9875 ppm for fig leaves. From the IC50 value, both the fruit and fig leaves are classified into a solid antioxidant compound. The antibacterial test results showed that the highest inhibitory diameter was found at a 100% concentration of 28.5 mm. The quantitative antibacterial activity test showed that the methanol extract of fig fruit had a MIC value at a concentration of 80% and a MKC value at a concentration of 100%. The optimal strength as an antibacterial from fruit extracts and leaves is 100% concentration. Conclusion : The results showed the methanol extract of fig (Ficus carica L.) has potential as an antioxidant and antibacterial compound.Keyword : Antioxidant, Antibacterial , Fig Plants